2021
DOI: 10.1097/shk.0000000000001756
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokine Profile Reveals Resistin Forming a Prognostic-Related Cytokine Network in the Acute Phase of Sepsis

Abstract: Introduction: Cytokines compose a network and play crucial roles in the pathogenesis and prognosis of sepsis. Adipose tissue is an important immune endocrine organ that releases adipocytokines. This study aimed to evaluate adipocytokines in sepsis from a network perspective. Materials and Methods: This retrospective study of 37 patients with sepsis and 12 healthy controls was conducted from February 2014 to July 2015. Blood samples were collected from patients on days 1 (within 24 h of diagnosis), 2, 4, 6, 8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…In the present study, the resistin gene expression in whole blood cells was elevated, suggesting that these cells were responsible for the production of resistin in COVID-19 patients. Resistin is reported to play a role as a pro-in ammatory cytokine [24] and to be related to the pathogeneses of cardiovascular disease [25], cancer [26] and sepsis [13,14,27]. In the present study, COVID-19 patients showed increased plasma resistin levels (although these levels were lower than those in sepsis patients) and resistin, cytokines and endothelial damage markers formed a network.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In the present study, the resistin gene expression in whole blood cells was elevated, suggesting that these cells were responsible for the production of resistin in COVID-19 patients. Resistin is reported to play a role as a pro-in ammatory cytokine [24] and to be related to the pathogeneses of cardiovascular disease [25], cancer [26] and sepsis [13,14,27]. In the present study, COVID-19 patients showed increased plasma resistin levels (although these levels were lower than those in sepsis patients) and resistin, cytokines and endothelial damage markers formed a network.…”
Section: Discussionmentioning
confidence: 45%
“…In vitro, resistin has been shown to induce the nuclear translocation of NF-kB transcription factors in macrophages and to lead to the increased expression of several pro-in ammatory cytokines, including IL-1, IL-6, IL-12 and TNF-α, in both mice and humans [28]. In a study of sepsis patients, resistin was reported to compose a strong network with IL-6, IL-8 and MCP-1 during the acute phase, and that network was reported to be related to the severity and prognosis of sepsis [14]. Second, resistin directly activates vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last step, we re ned our analysis by seeking the correlation-based networks of cytokines and vascular mediators. It is well known that the levels of several cytokines can predict the clinical course, severity, and prognosis of different in ammatory diseases, mainly in the acute phase of sepsis [29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Various adipokines, i.e., hormones derived mainly from the adipose tissue, exert immunomodulatory actions, being implicated in the inflammatory response during sepsis [ 31 , 32 , 33 , 34 ]. Previous studies have highlighted that circulating adipokines are altered during sepsis in critically ill patients and may serve as diagnostic and prognostic biomarkers [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%